A Chemical Potential Equation for Modeling Triboelectrochemical Reactions on Solid–Liquid Interfaces - Liu, Chenxu; Tian, Yu; Meng, Yonggang (Frontiers in Chemistry, 2021)
Triboelectrochemical reactions occur on solid-liquid interfaces in wide range of applications when an electric field strong enough and a frictional stress high enough are simultaneously imposed on the interfaces. A characteristic of triboelectrochemical reactions is that not only the thermal energy but also the electrical and mechanical energies can activate, assist or mitigate the solid-liquid interface chemical reactions, the products of which affect electrical and tribological behavior of the interfaces inversely. In previous studies, we have found that the coupling of frictional and electric effects could physically change the migration, adsorption and desorption behaviors of the polar molecules, ions or charged particles included in aqueous or nonaqueous base lubricant towards or away from the interfaces, and thus control the boundary lubrication. Recently, we have found that the friction coefficient and surface appearance of some kinds of metals could also be modulated to some extent even in pure water or pure base oils under external electric stimulations. We attribute these changes to the triboelectrochemical reactions occurred when a strong external electric field is imposed on. Based on the effective collision model of chemical reactions, a chemical potential equation, which includes both electrical and mechanical contributions, has been derived. The proposed chemical potential equation can be used to explain the observed triboelectrochemical phenomenon in experiments. Based on the model, a novel method for oxidation coloring of the selected areas in metal surfaces is proposed. Together with the physical adsorption and desorption model of lubricant additives, the triboelectrochemical reaction model can well explain the phenomena of potential-controlled boundary lubrication in different lubrication systems, and also provides a theoretical basis for other solid-liquid interface processes under the effects of electro-mechanical coupling.